Anti-gravity treadmill training benefits the post-operative rehabilitation of ACL reconstruction and the effects on the muscular atrophy and balance ability: a cohort study and 1y follow-up - Ma, Bing-Xian; Qi, Yan-Song; Zhang, Zi-Heng; Tian, Ye (Frontiers in Sports and Active Living, 2025)
BackgroundPost-operative muscular atrophy and impaired balance are great rehabilitation challenges in patients with anterior cruciate ligament reconstruction (ACLR). Anti-gravity treadmill training (AGTT) is a novel rehabilitation therapy that provides partial body-weight support (BWS) and enhances muscular motor. The present study aims to explore the effects of AGTT rehabilitation on muscular atrophy and balance ability, as well as the outcomes of knee function, physical activity, and return to sports in ACLR patients.MethodsThis was a prospective cohort study. ACLR patients were included between January 1, 2022, and December 31, 2023, and randomly divided into the AGTT group (6-week AGTT+routine rehabilitation protocol) and control group (routine rehabilitation protocol). After a 6-week AGTT, a muscular atrophy grading system was used to estimate the severity of quadriceps femoris atrophy, and the Berg balance scale (BBS) was used to evaluate the patients’ balance ability. At 1y follow-up, the outcome functional assessments were performed, including Lachman and pivot shift test, A-P ligament laxity (KT-2000), range of motion, International Knee Documentation Committee (IKDC) score, Tegner Activity Score (TAS), and rate of returning to sports.Results73 ACLR patients have completed 1y follow-up, the total missing rate was 8.75%. After 6-week AGTT, the severity of quadriceps femoris atrophy was significantly decreased in the AGTT group (18/36, grade A/all) than the control group (7/37, P = 0.003), while the BBS in the AGTT group (53.67 ± 1.00) was significantly increased than the control group (52.12 ± 1.08, P < 0.001). At 1y follow-up, the A-P joint stability (22/36, normal/all), IKDC (81.61 ± 6.92), TAS (3.64 ± 0.76), and the rate of return to sports (26/36, yes/all) in AGTT group were significantly higher than the control group (10/37, P = 0.015) (78.63± 2.75, P = 0.020) (3.14± 0.75, P = 0.006) (16/37, P = 0.012).ConclusionsA 6-week AGTT rehabilitation can protect the quadriceps femoris muscular atrophy and promote balance recovery in ACLR patients, resulting in better short-term outcomes of joint stability, knee function, physical activity level, and return to sports.Level of evidenceLevel 2.